SLEEP QUALITY AND BLOOD PRESSURE IN HYPERTENSION PATIENTS UNDERGOING HEMODIALYSIS - Simanjuntak, Edriyani Yonlafado; Sipayung, Normi Parida; Syapitri, Henny; Hulu, Juli Jernih (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Background: Hypertension or increased blood pressure is a silent killer disease whose main cause is currently unknown. High blood pressure is the highest case with an incidence reaching 22% of the world's population, or around two-thirds of hypertension sufferers coming from countries with lower-middle incomes. One of the factors causing hypertension or increased blood pressure is poor sleep quality. Purpose: The objective of this was to identify the relationship between sleep quality and blood pressure in hypertensive patients undergoing hemodialysis Methods: The study was a quantitative survey with a cross-sectional approach in a population of End State Renal Disease patients with hypertension underwent hemodialysis at RSUP. H. Adam Malik, Medan. A total of 57 individuals were sampled using a purposive sampling technique. The measuring instrument uses a questionnaire and a digital tensiometer. Univariate and bivariate data were obtained from statistical analysis using a computer. Results: Statistical tests used Spearman rank. The outcomes of the study showed the average score of respondents' sleep quality was 13.16, meaning poor sleep quality, and the average systolic blood pressure was 147.26 mmHg, meaning grade 1 (mild) hypertension, and diastolic blood pressure was 93.81 mmHg, meaning grade 1 (mild) hypertension. Statistical tests showed a significant value of p-value = 0.000 (α <0.05), This means there are relationship between sleep quality and blood pressure in hypertensive patients undergoing hemodialysis. Conclusion: It is recommended that health workers improve the quality of their services by providing education to have good sleep quality and controlled blood pressure.